Sistem Informasi Donasi Online Berbasis Website - Sri Mulandari; Yuni Fitriani; Sri Utami; Bambang Junadi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
In today's era, computer technology is experiencing an increase in a very rapid number. This is because computer technology is an important factor in an agency both private and government. The development of technology is also very influential in today's life, especially information technology which is very helpful in solving various problems in various fields. Please help each other is the duty of every human being in the event of natural disasters, donations, providing assistance to the unable, and others. The number of people in various regions help each other in their own way such as raising funds at red light intersections, around people's homes, or to several private agencies. Not all foundations or institutions can realize their desire to have their own special foundation or institution website. There are still foundations or institutions that use books and process data using microsft excel which is less effective and efficient. In addition, the submission of reports on the use of funds to donors is also often hampered, causing distrust of donors to foundations or institutions regarding the management of donations and donations. Therefore, the author wants to create a program that makes it easier for people to make donations or raise funds by creating a website with the title